Research framework of studying trade integration of the Eurasian Economic Union - Pavlovskaya, Svetlana V. (Journal of the Belarusian State University. Economics, 2018)
Historically, interstate trade is a primary and mostly spread channel for implementing world economic ties. There is a rich research framework for studying integration processes and trade integration in particular. The different approaches  and methods for analysing integrative interaction within the framework of the Eurasian Economic Union (EEU) are presented, the main factors affecting the economic cooperation of the EEU member countries are identified (geopolitical factors (“a new geopolitical situation”); economic factors (differences in the structure of national economies, systemic crisis phenomena, dominant position of Russia as a trade and economic partner); the neighborhood factor (presence of traditional relations, common historical past, cultural relations), and an attempt to understand the instruments for analysing trade integration in complex is made in the article. Research of commodity structure of mutual trade of the EEU member countries can be considered as the main method of studying the dynamics of integration processes and identifying the prospects for their development. This will not only reveal the main trends of integration, but also geographical and in dustry prerequisites for the development of production cooperation within the framework of the EEU. Within the framework of the study of trade integration, gravity models play a special role as econometric implementation of the gravity model allows to determine the potential levels of intraregional trade, they complement the vision of the results and opportunities for trade integration.
Keywords: international economic cooperation; trade integration; the Eurasian Economic Union; intraindustry specialization; foreign trade quota; international trade; gravity model